2018
DOI: 10.1364/oe.26.010519
|View full text |Cite
|
Sign up to set email alerts
|

Real-time 100 Gbps/λ/core NRZ and EDB IM/DD transmission over multicore fiber for intra-datacenter communication networks

Abstract: A BiCMOS chip-based real-time intensity modulation/direct detection spatial division multiplexing system is experimentally demonstrated for both optical interconnects. 100 Gbps/λ/core electrical duobinary (EDB) transmission over 1 km 7-core multicore fiber (MCF) is carried out, achieving KP4 forward error correction (FEC) limit (BER < 2E-4). Using optical dispersion compensation, 7 × 100 Gbps/λ/core transmission of both non-return-to-zero (NRZ) and EDB signals over 10 km MCF transmission is achieved with BER l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Extensive work has been reported on SDM transmission carrying different modulation formats on DCN links, including NRZ [75][76][77], EDB [75][76][77], PAM4 [78][79][80][81] and DMT [24,82]. In [77], a BiCMOS chip-based real-time 100Gbps/λ/core NRZ and EDB over 10km 7-core MCF SDM interconnects is experimentally demonstrated. The integrated low complexity transceiver circuits and simple signal processing approach make such a system cost-efficient for the high-speed DCN interconnects.…”
Section: B Modulation Formats and Dspmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive work has been reported on SDM transmission carrying different modulation formats on DCN links, including NRZ [75][76][77], EDB [75][76][77], PAM4 [78][79][80][81] and DMT [24,82]. In [77], a BiCMOS chip-based real-time 100Gbps/λ/core NRZ and EDB over 10km 7-core MCF SDM interconnects is experimentally demonstrated. The integrated low complexity transceiver circuits and simple signal processing approach make such a system cost-efficient for the high-speed DCN interconnects.…”
Section: B Modulation Formats and Dspmentioning
confidence: 99%
“…To mitigate the linear impairments, linear adaptive filtering based equalizations (e.g. least-squares LS [24], FFE [77,81], decision feedback equalization DFE [78,81], and maximum likelihood sequence estimate MLSE [88]) work well. To mitigate the nonlinear impairments, nonlinear equalizations are required.…”
Section: B Modulation Formats and Dspmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous research, we concluded that intensity nonreturn-to-zero on-off keying (NRZ-OOK) modulation format, as well as 4-level amplitude modulation PAM-4 modulation format, which has higher spectral efficiency and potentially can provide higher data transmission speeds in fiber optical networks with limited bandwidth, are still affected with the chromatic dispersion (CD), which is one of the main distance-limiting factors [10], [11]. In particular, the most common solution due to a cost-effective way is reuse the already developed and used commercially available components operating at 10 Gbit/s PONs (10G PON) technology for the desired NG-PONs at least increases bitrates for 25 Gbit/s either 40 Gbit/s per channel [12].…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the emerging of 5th-Generation network, cloud services, quantum secured network [1], [2], spatial division multiplexing (SDM) technology has grown rapidly over the past decade, from short-reach to long-haul optical fiber telecommunication systems. Weakly coupled multicore fiber (WC-MCF) based intensity modulation/direct detection (IM/DD) systems are very promising for application in low-cost/high density parallel signal-mode core links, ultrahigh-density trunk/outside plane cables [3], and intra-or inter-datacenter interconnects [4], [5]. To reach the maximum system capacity, one method is the inclusion of as many cores as possible in the MCF.…”
Section: Introductionmentioning
confidence: 99%